1995
DOI: 10.1063/1.115259
|View full text |Cite
|
Sign up to set email alerts
|

Giant Hall effect in percolating ferromagnetic granular metal-insulator films

Abstract: We studied both the resistivity and the Hall resistivity of cosputtered granular Ni–SiO2 films with the metal volume fraction x in the range of 0.5–1.0. Near the metal-insulator transition, or x of about 0.53–0.61, the saturated value of the Hall resistivity was up to 2×10−4 Ω cm. This value is almost 4 orders of magnitude greater than that of pure nickel. Both the resistivity and the Hall resistivity varied weakly with temperature, throughout the range of 5–300 K. We suggest that the percolating ferromagnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
121
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(130 citation statements)
references
References 2 publications
6
121
0
3
Order By: Relevance
“…Thus, in granular metals, as the metal concentration decreases, the lower carrier density is expected to yield an enhanced Hall coefficient which peaks at the percolations threshold with a factor of ϳ30 for ϳ1 mm thick films [1,2]. Recently, however, it was found that in the magnetic ͑NiFe͒-SiO 2 , and Fe-SiO 2 granular films [2][3][4][5], the extraordinary Hall coefficient was enhanced by a factor of 10 4 when the metal volume fraction is close to x 0.53 (the classical percolation threshold). An especially intriguing feature of this discovery is that, even after magnetic saturation, the ordinary Hall coefficient was still observed to increase by almost 3 orders of magnitude [4], suggesting a magnetic-independent mechanism could be operative.…”
mentioning
confidence: 99%
“…Thus, in granular metals, as the metal concentration decreases, the lower carrier density is expected to yield an enhanced Hall coefficient which peaks at the percolations threshold with a factor of ϳ30 for ϳ1 mm thick films [1,2]. Recently, however, it was found that in the magnetic ͑NiFe͒-SiO 2 , and Fe-SiO 2 granular films [2][3][4][5], the extraordinary Hall coefficient was enhanced by a factor of 10 4 when the metal volume fraction is close to x 0.53 (the classical percolation threshold). An especially intriguing feature of this discovery is that, even after magnetic saturation, the ordinary Hall coefficient was still observed to increase by almost 3 orders of magnitude [4], suggesting a magnetic-independent mechanism could be operative.…”
mentioning
confidence: 99%
“…The highest room temperature EHE resistivity of about 200 µcm, named the Giant Hall effect [9], was found in granular ferromagnetic mixtures, such as Ni-SiO2 [9,10] and CoPtSiO2 [4], in vicinity of the conductance percolation threshold. It was therefore concluded [4] that while EHE can readily be used for micrometer and larger devices, no materials are yet available which offer suitable scalability towards the nanometer size microelectronic node.…”
mentioning
confidence: 99%
“…The highest room temperature resistivity typically observed in such films is 0.1 -1 mcm, and EHE resistivity is 1-10 µcm [11]. Three-dimensional granular films, composed of immiscible metallic ferromagnet and insulator mixtures, reach geometrical percolation threshold when the insulator volume content exceeds 40-50% (80% in random metal-insulator mixtures) with characteristic values of longitudinal and EHE resistivities of 1 cm and 100 µcm respectively [9]. In this work we explored a different approach to fabrication of low conductance films: we start with amorphous To remind, Hall resistance in magnetic films can be presented as:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 All these enhanced physical properties are related to electron conduction in the vicinity of the percolation threshold. Macroscopic measurements have made a considerable contribution to our understanding of the percolation phenomenon.…”
mentioning
confidence: 99%